Penerapan Alat Pelindung Diri (APD) di Laboratorium Tata Boga, Universitas Negeri Makassar - Muliani, Muliani; Ratnawati T; Simaremare, Perawati; Niza, Andi Khaerun; Isnaeni, Rizki (Jurnal Edukasi dan Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of first-year students in the proper use of Personal Protective Equipment (PPE) in the laboratory for the Basic Culinary course. The application of PPE serves as a preventive measure to reduce workplace accidents, maintain hygiene, and enhance safety awareness within vocational education environments. The implementation methods included socialization, demonstration, hands-on training, and evaluation of PPE usage among early-semester students. The results indicated an increase in students’ knowledge by 34% after the training, as well as an improvement in PPE compliance from 62% to 95%. Data analysis using a descriptive quantitative approach and direct observation demonstrated that the training was effective in strengthening work safety discipline. This activity is expected to serve as a safety-based practical learning model in culinary laboratory settings.